Analysis of two whale shark watching destinations in Indonesia: status and ecotourism potential - ASRIL DJUNAIDI; Jamaluddin Jompa; Nadiarti Nurdin Kadir; Ahmad Bahar; Sukirman DJ Tilahunga; Deborah Lilienfeld; Maulita Sari Hani (Society for Indonesian Biodiversity, 2020)
Abstract. Djunaidi A, Jompa J, Nadiarti N, Bahar A, Tilahunga SD, Lilienfeld D, Hani MS. 2020. Analysis of two whale shark watching destinations in Indonesia: status and ecotourism potential. Biodiversitas 21: 4511-4523. Botubarani in Gorontalo, on the northern coast of Tomini Bay and Labuhan Jambu in Teluk Saleh, Sumbawa recently became whale shark tourism destinations in Indonesia. Both sites offer visitors opportunities to interact with whale sharks, either watching from canoes or snorkelling and diving. In this study, we investigated the status and ecotourism potential of whale shark watching as a form of marine wildlife tourism development in eastern Indonesia by examining the existing operations in both sites. Data were collected using questionnaires administered to local community members and visitors to understand their perceptions, and how this opportunity was valued. Secondary data were collected to explore and understand influencing factors. Findings revealed that whale sharks commonly emerge near bagan lift-nets and other interactive areas as a response to the presence of their favorite prey, anchovies, and rebon shrimp. In general, whale sharks most commonly visit bagan lift nets and can be found in the interaction areas in the morning and stay for couple of hours before swimming away to deeper waters. Out of 119 community respondents in Labuhan Jambu village (Teluk Saleh) and Botubarani, Gorontalo, 80.7% knew about the occurrence of whale sharks in their locality. Of the 111 visitor respondents, 67.6% knew about the whale shark watching sites from word of mouth. The study results also suggest a correlation between chlorophyll-a concentration, anchovies, rebon shrimp and whale sharks. Regarding management approaches to this type of tourism, a local community-based management model is strongly recommended, with 87.4% of respondents showing interest in this approach. The roles and responsibility of local government in developing such tourism is very significant, especially with respect to facilitating appropriate competency within the local community throughout training and education, as suggested by nearly 26% of respondents.